MULTIWIRE DRIFT TUBES WITH JET-CELL GEOMETRY FOR MUON DETECTION AT LHC - Bagnaia, P; Barberio, E; Beker, H; Bilokon, H; Borisov, A; Bozhko, N; Chiarella, V; Ciapetti, G; Curatolo, M; Dris, M; Esposito, B; Fabjan, C; et al. (1995)
Recent results from test measurements with cosmic rays of jet-cell chamber prototypes, developed and studied for the mu, detector of the ATLAS apparatus, are reported.